Sufficient manganese supply is necessary for OsNramp5 knockout rice plants to ensure normal growth and less Cd uptake - Muhammad Shahzad; Di Peng; Ameer Khan; Ahsan Ayyaz; Syed Muhammad Hassan Askri; Shama Naz; Binbin Huang; Guoping Zhang (Ecotoxicology and Environmental Safety)
The development of crop cultivars with less Cd uptake in roots and accumulation in shoots is a most efficient and environment-friendly approach to deal with soil Cd contamination. Recently repression of Nramp5 expression or its knockout is commonly recognized to be efficient for reducing Cd accumulation in plants, but such mutant plants suffer from manganese deficiency. In this study, we assessed the efficacy of exogenous Mn addition in mitigating Cd stress in a japonica rice cultivar Xidao 1 (Wild Type, WT) and its OsNramp5 knockout mutant. Exposure to Cd stress resulted in notable low photosynthetic rate, growth inhibition, and high Cd accumulation in rice seedlings. Although the mutant plants contained much lower Cd concentration in both roots and shoots than the WT plants, their growth was significantly inhibited relative to the WT plants under the normal condition. Exogenous application of Mn (40 μM) dramatically reduces root and shoot Cd concentrations and alleviates the toxic effect of Cd stress in both rice types, with the mutant plants demonstrating lower Cd concentration and less Cd toxicity in comparison with WT plants. The alleviation of Cd toxicity by Mn addition was more effective in higher Cd level (1.0 μM) than in lower Cd level (0.1 μM). Mn increases the expression of OsNramp5 and other genes, including OsHMA2, OsHMA3, OsIRT1, and OsIRT2, which encode ion transporters related to Mn uptake and transportation, and meanwhile reduces Cd uptake and accumulation in rice seedlings. In short, the knockout of OsNramp5 results in the significant reduction of Cd uptake, but accompanies with Mn deficiency in rice plants, which can be efficiently overcome through exogenous Mn addition.